Modernism in graphic design (Journal of Namibian Studies : History Politics Culture, 2023)
Given that graphic design is part of this movement as a renewed art based on ((returning to the logic of old artistic methods and trends, neither at the level of form nor at the level of technology with all its rich legacy of all standards)) (Moataz, 2020, p. 102) and because modernity has legislated for the art of graphic design new data on the intellectual, material and technical level, as it cannot be counted because it is not limited to time or place. Modernism ((is a reference to a neutral view of art as an expression or as a method of using language and a degree of ambiguity that exceeds the expectations and feelings of the ordinary reader)) (Brooker, 1995, p. 20). The concept of modernity is ((a deep structural change in the individual and society in thought, system, and civilization)) (Sharabi, 1993, p. 30), and it means that modernity transcends all restrictions and borders and is considered a comprehensive movement that is multiple and contradictory at the same time, because it deals with ((The designer's relationship with himself, and on the other hand, the designer's relationship with the outside world, and then all the social, psychological, economic and political transformations cast a shadow on the nature of the relationship between the designer and his work)). (Al-Qara Ghuli, 2006, pg. 9).